A criterion for failure mode prediction of angle-ply composite laminates under in-plane tension. (15th September 2015) - Dong, H.; Wang, J.
Abstract: As the failure of fibre-reinforced angle-ply composite laminates involves basic features of failure of general laminates, its understanding and prediction are of fundamental importance. In this paper, a criterion for predicting the failure mode of angle-ply laminates under in-plane tension is presented. The criterion is able to predict the two different modes of the final failure of angle-ply laminates found in previous experiments: the pull-out of the internal layer due to transverse cracks and delaminations with no fibre breakage, and a single crack across the width of the laminate. The theoretical results demonstrate that the final failure mode of an angle-ply laminate is determined by the value of a failure factor which is related to the thickness and strength of the lamina, the width and ply angle of the laminate, and the interface strength. The pull-out failure occurs when the failure factor is greater than one, and the single cracking occurs when it is less than one. The criterion also shows that the final failure of angle-ply laminates exhibits size effects both in the thickness direction and the width direction. Moreover, the criterion is extended and applied to general angle-ply laminates. The theoretical predictions agree with experimental results.